A rare coexistence: Cecal cancer and intestinal malrotation in an adult - Hind Qajia, MD; Chaimaa Jabbari, MD; Salma EL kadiri, MD; Choumad Saleck, MD; Yassine Eddahoumi, MD; Fatima Ezzahra Laamrani, PhD; Omar EL Aoufir, PhD; Laila Jroundi, PhD (Radiology Case Reports)
Intestinal malrotation (IM) is an uncommon congenital disorder that disrupts the normal embryonic rotation around the superior mesenteric artery. It is exceptionally rare in adults, and its association with colon cancer is even less frequent. This article discusses the case of a 60-year-old female diagnosed with colon cancer alongside IM. Imaging studies revealed signs of IM. This case highlights the rarity of colon cancer occurring in a malrotated bowel, emphasizing the importance of early detection to prevent life-threatening complications. This anomaly increases the risk of volvulus, bowel obstruction, and ischemia. Diagnosis often relies on imaging techniques, such as CT or ultrasound, to identify abnormal intestinal orientation.